Prevalence and correlates of destructive behaviors in the US Naval Surface Forces from 2010–2020 - Kevin Lai; Jason T. Jameson; Dale W. Russell (BMC Psychology, 2023)
Abstract Purpose To estimate the prevalence of domestic violence, sexual assault, and suicide for United States Navy (USN) personnel between 2010 and 2020 and identify potential associated factors. Methods Official report data were used to calculate prevalence rates and odds ratios, accounting for sample and general USN population demographic data to assess differences in over- or underrepresentation of destructive behaviors. Results Domestic violence and sexual assault offenders tended to be younger lower-ranked males. For sexual assaults, offenders were three times more likely to be senior to the victim, which was not the case for domestic violence. Females were overrepresented in terms of suicidal ideation and attempts relative to the USN population, while males accounted for more actual suicides. The relative rates of suicidal ideation and attempts for females exceeded those for males (i.e., comparing the sample rate against the USN male and female populations), but the sample proportion for completed suicides (compared to the USN population) were greater for males than for females. Those in the junior enlisted (E1–E3) paygrades exhibited greater odds of suicide attempts versus suicidal ideations relative to those in the Petty Officers (E4–E6) paygrades, although E4–E6s completed more suicides. Conclusion The descriptive profile of destructive behaviors in a representative sample of USN personnel provides an overview of the possible factors associated with destructive behaviors and includes an exploration of the relational dynamics and nature of the incidents. The results suggest that sexual assault and domestic violence are characterized by unique relational dynamics and that these destructive behaviors should not necessarily be classified together as male-oriented aggressions (i.e., mainly perpetrated by males against female victims). Those in the E1–E3 and E4–E6 paygrades displayed different patterns in suicidal ideation, attempts, and actual suicides. The results highlight individual characteristics to help inform the development of targeted policies, practices, and interventions for military and other hierarchical organizations (e.g., police).